(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
In the article, the interdisciplinary linkage, which has become the actual topic of the day, has been highlighted, especially in the methodology of Foreign Language Teaching, the interdependence of the effective use of gaming and information technologies within the framework of primary classes, the advantages of which have been highlighted.On the basis of interactive techniques, the rules for a wider coverage of language skills are expressed